Monitoring of Flower Visiting Insects on Buckwheat (Fagopyrum Esculentum Moench.) in Chitwan, Nepal - Aryal, L.N.; Thapa, R.B.; Tiwari, S.; Chaudhary, N.K. (International Journal of Applied Sciences and Biotechnology, 2016)
This paper presents the finding of the field experiment conducted on monitoring of flower visiting insects on buckwheat (Fagopyrum esculentum Moench.) at farmers’ field during winter, 2012/13 at Meghauli, Chitwan, Nepal. The abundance and distribution of flower visiting insects were studied by monitoring with insect net and pan traps at 500 m, 1500 m and 2800 m from the natural habitat (forest). The wild insects (wasps and Apis dorsata F.) were found higher near to natural habitat and domesticated insects (Apis mellifera L. and Apis cerana F.) found more away from the natural habitat or close to housing and apiaries. Besides, Apis florea F., Andrena sp., Synoeca sp., Chalcid sp., Formica sp., Syrphus sp. and various Dipteran, Coleopteran, and Lepidopteran were also the flower visitors of buckwheat close to natural habitat. So, the diversity index varied with distance from the natural habitat, i.e. increase on proximity to natural habitat, i.e. 1.11, 1.25 and 1.62 at 2800 m, 1500 m and 500 m, respectively on sweeping with insect net and 0.65, 1.04 and 1.30 at 2800 m, 1500 m and 500 m, respectively on setting pan traps. Thus, the number and diversity of flower visiting insects get increased on proximity to natural habitat suggesting either conservation of natural habitat (forest) near farming communities or shifting of buckwheat cultivation near to natural habitat for adequate pollination and production. Int J Appl Sci Biotechnol, Vol 4(3): 380-385